STRATEGI KOMUNIKASI BAWASLU KOTA TANGERANG DALAM UPAYA PENINDAKAN PELANGGARAN KAMPANYE PEMILIHAN PRESIDEN 2019 - Lina Wati (Universitas Prof. Dr. Moestopo (Beragama), 2020)
This study aims to discuss the communication strategy of the Tangerang City Election Supervisory Agency in the effort to suppress campaign violations in the 2019 Presidential Election. It is known that the spread of the Barokah Tabloid in Baiturahman Mosque, Karawaci Subdistrict, Tangerang City is a violation of the 2019 ELECTION campaign in places of worship. This research uses a qualitative approach with a case study method and in data collection using interviews and documentation. Research Findings Analyzing the findings of the Barokah Indonesia tabloid which spread in Kawaraci in the mosque, identified these findings and traced these findings. Tangerang City Bawaslu Communication Strategy Coordinate with various parties and provide oversight of the implementation especially the 2019 election campaign especially in the Karawaci area and the implementation of activities in places of worship.